As stated in the statement, we will apply energy conservation to solve this problem.
From this concept we know that the kinetic energy gained is equivalent to the potential energy lost and vice versa. Mathematically said equilibrium can be expressed as
Where,
m = mass
= initial and final velocity
g = Gravity
h = height
As the mass is tHe same and the final height is zero we have that the expression is now:
Expression to calculate energy from voltage: E= V*Q where E= energy, V= voltage, and Q= charge
Additional help:
-To find the Voltage ( V )
[ V = I x R ] V (volts) = I (amps) x R (Ω)
-To find the Current ( I )
[ I = V ÷ R ] I (amps) = V (volts) ÷ R (Ω)
-To find the Resistance ( R )
[ R = V ÷ I ] R (Ω) = V (volts) ÷ I (amps)
I hope that helps to some extent-
Answer:
The answer would be B) The Same
Explanation:
Not gonna lie I checked my class notes but I figured this would help :)
Good luck!!!
Answer:
Explanation:
The speed of light is given by
and hence
Speed of light is given by